Molecular dynamic of omega-3 compounds as an anti-obesity agent into GPR-120 receptor - Ida Musfiroh; Ginna Megawati; Dewi Marhaeni Diah Herawati; Okta Nama Putra; Evi Sylvia Nurrasjid (Pensoft Publishers, 2023)
Obesity is a cause of comorbid diseases such as type 2 diabetes mellitus, dyslipidemia, hypertension which is based on low-level chronic inflammation. The GPR-120 receptor plays a role in insulin sensitization which is related to diabetes mellitus which is a comorbid obesity. Omega-3 fatty acids are believed to possess anti-inflammatory properties, hence potentially serving as a preventive measure against obesity-related comorbidities. The aim of this study is to do a stability analysis of the binding affinity between nine specific chemicals derived from omega-3 and the active site of the human GPR120 receptor using molecular dynamics simulations. Docking analysis was performed using Discovery Studio Visualizer, AutoDock Tools 1.5.6, and molecular dynamic simulation with AMBER 16. In this study, we used neurotensin 8-13 as a natural ligand to bind with the neurotensin receptor. Based on the neurotensin receptor docking results, the ΔG values for the following compounds are close to the values for neurotensin 8-13 -6.41 kcal/mol; docosahexaenoic acid -8.96 kcal/mol; eicosapentaenoic acid -7.41 kcal/mol; and heneicosapentaenoic acid -6.34 kcal/mol. Neurotensin 8-13 forms hydrogen bonds with TYR146, ARG213, and PHE344 of the neurotensin receptor, whereas docosahexaenoic acid forms hydrogen bonds with TYR146. Meanwhile, the average RMSD fluctuations for each system, namely docosahexaenoic acid, eicosapentaenoic acid, and heneicosapentaenoic acid, were 0.672, 0.437, and 0.650, respectively. The SASA of the neurotensin receptor-ligand complex showed similar fluctuations, with the average values for docosahexaenoic acid, eicosapentaenoic acid, and heneicosapentaenoic acid being 230.40, 229.89, and 230.20 nm2.